Introduction of the 13-valent pneumococcal conjugate vaccine in an isolated pneumococcal vaccine-naïve indigenous population. Issue 5 (18th August 2016) - Verhagen, Lilly M.; Rivera-Olivero, Ismar A.; Hermsen, Meyke; Sisco, María Carolina; Maes, Mailis; del Nogal, Berenice; Bogaert, Debby; Berbers, Guy A.M.; Hermans, Peter W.M.; de Jonge, Marien I.; de Waard, Jacobus H.
The introduction of pneumococcal conjugate vaccines (PCVs) has the greatest impact in populations that are most affected by pneumococcal carriage and disease, such as indigenous children [1]. Although ∼10% of the South American population consists of indigenous people living in remote settings, to our knowledge PCVs have not been evaluated in native South American children. The Warao people are an Amerindian population residing in wooden houses along the Orinoco River delta in Venezuela. Almost one-third of Warao children die during childhood and respiratory tract infections are a major cause of death [2]. This study is the first to evaluate the impact of 13-valent (PCV13) vaccination on nasopharyngeal colonisation rates and antibody response in PCV-naïve indigenous South American children. PCV13 catch-up regimens for children aged ≥24 months may need to include more than one vaccine dose http://ow.ly/lstI3023i2R